2022
DOI: 10.1186/s12931-022-02269-2
|View full text |Cite
|
Sign up to set email alerts
|

Can birth weight predict offspring’s lung function in adult age? Evidence from two Swedish birth cohorts

Abstract: Background Associations between birth weight (BW) and adult lung function have been inconsistent and limited to early adulthood. We aimed to study this association in two population-based cohorts and explore if BW, adjusted for gestational age, predicts adult lung function. We also tested adult lung function impairment according to the mis-match hypothesis—small babies growing big as adults. Methods We included 3495 individuals (aged 46.4 ± 5.4 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…It is probable that during this range, the fetal environment facilitates optimal lung development, characterized by adequate alveolar multiplication, sufficient surfactant production, and optimal growth of the pulmonary vascular system. 22,23 The presence of a nonlinear association beyond this range may indicate the presence of distinct physiological challenges, such as an elevated susceptibility to obesity and associated comorbidities, which could counterbalance the advantages of a higher birthweight in terms of lung function 15,24 . This discovery implies the existence of a threshold effect in the correlation between birthweight and lung function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is probable that during this range, the fetal environment facilitates optimal lung development, characterized by adequate alveolar multiplication, sufficient surfactant production, and optimal growth of the pulmonary vascular system. 22,23 The presence of a nonlinear association beyond this range may indicate the presence of distinct physiological challenges, such as an elevated susceptibility to obesity and associated comorbidities, which could counterbalance the advantages of a higher birthweight in terms of lung function 15,24 . This discovery implies the existence of a threshold effect in the correlation between birthweight and lung function.…”
Section: Discussionmentioning
confidence: 99%
“…21 A comprehensive review of existing literature underscores the consistent finding that individuals with low birthweight consistently exhibit lower lung function, which aligns with our own findings. 22 This implies that the influence of birthweight on lung development is not temporary but rather persists into later stages of life, potentially impacting the susceptibility to respiratory diseases and the decline in lung function observed between the ages of 40 and 70.…”
Section: Discussionmentioning
confidence: 99%
“…They found that both FVC and FEV 1 were significantly lower at higher altitude and that the FEV 1 /FVC ratio decreased because FEV 1 decreased proportionally more than FVC, thus impacting on the ability of a FR to identify the population with AO at a high altitude [ 17 ]. Potential mechanisms behind these changes in lung function include harsh living environment, poverty, low birth weight, exposure to HAP [ 18 20 ]; adapting to chronic hypoxia and the related increase in ventilation [ 17 ]. However, to the best of our knowledge, no study has focused on comparing spirometry criteria for AO at high altitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Low birth weight is a surrogate marker of poor fetal growth (intrauterine growth restriction; IUGR) and a risk for preterm birth. Initial evidence also indicates that children with IUGR are also at risk for lung function trajectories below average and at risk for chronic lung disease later in life [ 16 , 17 ]. Studies conducted in rodents also suggest that perinatal insults predispose to pulmonary vascular dysfunction in adulthood.…”
Section: A Link Between Fetal-neonatal Lung Disease and Risk Of Ph In...mentioning
confidence: 99%